Facilitating Academic Achievement of Students in Carbohydrate: Consideration of Jigsaw, Think-Pair-Share and Coop-Coop Cooperative Strategies - Emmanuel Edoja Achor; Gladys Uzezi Jack; Comfort Daiko (Journal of Research in Science and Mathematics Education (J-RSME), 2022)
Worried by the poor performance of students in organic chemistry, this study examined the comparative facilitative effects of Jigsaw, Think-pair-share and Coop-Coop Cooperative Instructional Strategies on Achievement of students’ in Carbohydrate aspect of Chemistry in Jalingo metropolis in Taraba State, Nigeria. The population of the study comprised 1936 Senior Secondary two students in all the 41 public schools in the study area. The sample consists of 322 students (184 boys and 138 girls). Achievement Test in Carbohydrate (ATC) made up of 50 multiple choice questions was used to collect data for the study. Kuder-Richardson (K-20) was used to estimate the reliability index of 0.86 for the ATC. To answer the research questions and test hypotheses, the research adopted the descriptive statistics (Mean, and standard deviation) and inferential statistics of Analysis of Covariance (ANCOVA). Based on the data collected and analyzed, it was found that students taught carbohydrates using Jigsaw cooperative instructional strategy performed significantly better than their counterparts taught using Think-pair-share and Coop-Coop Cooperative Instructional Strategy. There was no significant difference between the mean achievement scores of male and female students taught carbohydrates using Jigsaw, Think-pair-share and coop–coop cooperative instructional strategies. Interaction effects between instructional strategies and gender on achievement was not statistically significant. It was recommended that there should be workshop to address the use of Jigsaw to teach chemical concepts and operations to enable teachers of chemistry employ it. Chemistry teachers should give female and male students equal opportunities in the classroom to enable them achieve equally.